Analisis Pemikiran KH. Ahmad Dahlan dalam Pendidikan Islam dan Relevansinya pada Pembelajaran Abad 21 - Nurdiyanto Nurdiyanto; Septia Nur Saputri; Ofik Taufiqurrohman; Amirul Haq Maqdum Wildany (Universitas Garut, 2025)
This study aims to analyze (1) the biography of KH. Ahmad Dahlan; (2) the works of KH. Ahmad Dahlan; (3) his concepts of education; and (4) his contributions to contemporary Islamic education. The research employs a qualitative approach, utilizing a library research method, and draws on various sources, including journals, e-books, websites, magazines, newspapers, proceedings, and other online media. Data analysis was carried out through descriptive analysis, namely by carefully comparing and interpreting the collected information. The findings affirm that KH. Ahmad Dahlan’s educational concept encompasses the definition, objectives, methods, materials, the roles of educators and learners, as well as the foundation of progressive education. His approach emphasizes not only religious aspects but also holistic learning relevant to the 21st century, including character development, critical literacy, collaborative skills, and adaptability in the face of scientific and technological advancements. In this way, KH. Ahmad Dahlan initiated educational reforms that promote holistic learning, integrating both religious and general knowledge within the framework of Islamic education as Rahmatan lil-‘alamin (a mercy for all creation)